(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article deals with the concept of crime and its indicators. The total volume of crimes in the Russian Federation is estimated. A multi-factor analysis was carried out and the dynamics of crimes committed in 2005-2019 was studied.